Penurunan Kadar BOD dan COD Limbah Cair Dengan Sistem Coarse Screen, Sedimentasi, Biofilter Anaerob-Aerob - Siti Rabiatul Adawiyah; Syarifudin A.; Munawar Raharja (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2020)
Waste from abattoir activities has high organic matter content. One wastewater alternative that suitable for abattoirs is used to utilize a combination of the anaerobic biofilter and aerobic biofilter. Which including a coarse screen, sedimentation, anaerobic biofilter, and aerobic biofilter. It made the treatment system can reduce levels of BOD snd COD waste batters. This study aims to determine the difference between the residence time variations of aerobic biofilter in reducing the BOD and COD levels of wastewater from abattoirs. The research is experimental. Using one group pretest-posttest design. Data analysis used the analysis of variance = 0,05.The analysis result of BOD and COD content wast decreased after treatment at each residence time, with 6 hours of residence time in an aerobics biofilter was reduced 70 percent BOD levels and 66,2 percent COD. 24 hours residence time had the ability to reduced 80 percent BOD content and 7 percent of COD content.Based on a one way analysis of variance results that there is a significant difference from all residence time because of Pvelue (0,00